Calcium-sensing receptor (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The calcium-sensing receptor (CaS, provisional nomenclature as recommended by NC-IUPHAR [44]) responds to multiple endogenous ligands, including extracellular calcium and other divalent/trivalent cations, polyamines and polycationic peptides, L-amino acids (particularly L-Trp and L-Phe), glutathione and various peptide analogues, ionic strength and extracellular pH (reviewed in [74]). While divalent/trivalent cations, polyamines and polycations are CaS receptor agonists [14, 106], L-amino acids, glutamyl peptides, ionic strength and pH are allosteric modulators of agonist function [34, 44, 58, 104, 105]. Indeed, L-amino acids have been identified as "co-agonists", with both concomitant calcium and L-amino acid binding required for full receptor activation [143, 51]. The sensitivity of the CaS receptor to primary agonists is increased by elevated extracellular pH [17] or decreased extracellular ionic strength [105]. This receptor bears no sequence or structural relation to the plant calcium receptor, also called CaS.